Soil Enzyme Activities and Yield of Elephant Foot Yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] as Influenced by Weed Management Practices in Alfisols - Manaswani, Moharana; K., Laxminarayana; M., Nedunchezhiyan (JOURNAL OF ROOT CROPS, 2020)
A field experiment was conducted during 2015-16 at the Regional Centre of ICAR-Central Tuber Crops Research Institute, Bhubaneswar, Odisha, India, to study the effect of various weed management practices on soil quality, microbial activities, and yield performance of elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] in an Alfisol. The results revealed that weed control ground cover resulted in lower weed biomass and greater weed control efficiency. Significantly higher corm yield was obtained with weed control ground cover treatment (37.4 t ha-1), with an increase of 335% over control, followed by four manual weedings at 30, 60, 90 and 120 days after planting (DAP) (33.7 t ha-1) and two manual weedings at 30 and 60 DAP along with post-emergence application of glyphosate at 90 DAP (32.9 t ha-1). Use of weed control ground cover resulted in higher post-harvest soil available N, P, K, Fe, Cu, Mn and Zn, microbial population (fungi, bacteria and actinomycetes) and soil enzyme (dehydrogenase, fluorescein diacetate, acid and alkaline phosphatase) activities. Two manual weedings at 30 and 60 DAP along with application of glyphosate at 90 DAP resulted in higher soil organic carbon.